Micrometer size polarisation independent depletion-type photonic modulator in silicon on insulator - Gardes, F.Y.; K. L. Tsakmakidis; Thomson, D.; Reed, G.T.; Mashanovich, G.Z.; Hess, O.; Avitabile, D. (Optics Express, 2007)
The trend in silicon photonics, in the last few years has been to reduce waveguide size to obtain maximum gain in the real estate of devices as well as to increase the performance of active devices. Using different methods for the modulation, optical modulators in silicon have seen their bandwidth increased to reach multi GHz frequencies. In order to simplify fabrication, one requirement for a waveguide, as well as for a modulator, is to retain polarisation independence in any state of operation and to be as small as possible. In this paper we provide a way to obtain polarisation independence and improve the efficiency of an optical modulator using a V-shaped pn junction base on the natural etch angle of silicon, 54.7 deg. This modulator is compared to a flat junction depletion type modulator of the same size and doping concentration. © 2007 Optical Society of America.